Applying the Plan–Do–Check–Act Quality Cycle to Improve Quranic Learning Using the UMMI Method - Eva Nurul Candra; Maya Nurfitriyanti (International Journal of Management, Innovation, and Education, 2024)
This study examines the implementation of the Plan–Do–Check–Act (PDCA) quality management cycle in Quranic learning using the UMMI Method at An-Nahl Islamic Kindergarten in Tangerang, Indonesia. The research aims to analyze how the PDCA model contributes to improving the quality of Quran learning through structured planning, execution, evaluation, and continuous improvement. Employing a qualitative descriptive design with case study and triangulated data collection techniques—observation, interviews, and documentation—the study explores each PDCA phase: planning (curriculum and method selection), doing (teacher training and instructional implementation), checking (performance monitoring and student achievement evaluation), and acting (continuous improvement based on assessment results). Findings reveal that the integration of PDCA with the UMMI method significantly enhances teaching effectiveness, student engagement, and memorization performance of short Quranic chapters. The approach also improves teacher competency through standardized certification and supervision by the UMMI Foundation. The study concludes that combining PDCA and the UMMI method provides a sustainable framework for quality assurance in Islamic education by fostering systematic planning, accountability, and continuous pedagogical improvement, contributing to the development of a Qur’an-literate and spiritually strong generation.